2011
DOI: 10.1590/s0100-40422011000600003
|View full text |Cite
|
Sign up to set email alerts
|

Fe (ii) adsorption on Ucides Cordatus crab shells

Abstract: Recebido em 13/5/10; aceito em 12/1/11; publicado na web em 29/3/11In this study Ucides cordatus crab shells were utilized as Fe (II) sorbent as material of low cost and simple preparation. Values of pH of standard solution, biosorbent mass, particles size, contact time (t c ) and initial concentration of the standard solution were optimized. The best conditions were pH = 2.00, t c = 840 min and M c = 0.25 g. The kinetic pseudo first-order model displayed the best description of the adsorption process and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…Azouaou et al 6 concluded that the Langmuir's isotherm model was in agreement with the experimental data obtained in the cadmium adsorption experiment on untreated coffee grounds. Porpino et al 12 also concluded that the iron adsorption by crab shell followed the model proposed by Langmuir. This variation depends on the analyzed material, because the adsorption process is linked to the adsorbent's free sites, where links with the metal occur, influencing both whether the process occurs in mono or multilayers.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…Azouaou et al 6 concluded that the Langmuir's isotherm model was in agreement with the experimental data obtained in the cadmium adsorption experiment on untreated coffee grounds. Porpino et al 12 also concluded that the iron adsorption by crab shell followed the model proposed by Langmuir. This variation depends on the analyzed material, because the adsorption process is linked to the adsorbent's free sites, where links with the metal occur, influencing both whether the process occurs in mono or multilayers.…”
mentioning
confidence: 85%
“…For the calculations, the same formulas employed by Porpino and Barreto 12 were used. The lead and cadmium adsorbed amount per adsorbate gram, Qe, was calculated using Eq.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
See 2 more Smart Citations
“…C eq q eq = 1 q m b + C eq q m em que: b -constante que indica a intensidade da biossorção q m -capacidade que indica a quantidade máxima adsorvida log q eq = log K f + 1 n log C eq em que: K f -constante de Freundlich, que está relacionada com a capacidade de biossorção n -constante que indica a intensidade de biossorção Se os valores de n estiverem na faixa 1 < n < 10, indicam uma biossorção favorável (Porpino et al, 2011).…”
Section: Methodsunclassified